The Influence of the Role-Playing Learning Model on Students' Communication Skills in Indonesian Language Learning at SD Negeri 091273 Karang Bangun - Sihombing, Rosben (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to analyze the effect of the Role Playing learning model on students' communication skills in Indonesian language learning at SD Negeri 091273 Karang Bangun. Communication skills are a crucial aspect in language learning, including listening, speaking, reading, and writing skills. The study used a quantitative approach with a One Group Pretest-Posttest Design. The research subjects were 25 fourth-grade students selected through a total sampling technique. The research instruments were a written test and a validated observation rubric. The results showed an increase in the average score from 49.8 (pretest) to 79.6 (posttest), with an n-gain value of 0.59 which is classified as moderate. In addition to the increase in scores, observations showed an increase in students' active involvement and self-confidence in the learning process. These findings indicate that the Role Playing model is effective in developing students' communication skills through contextual and meaningful role simulations. Thus, this model can be used as an innovative alternative strategy in Indonesian language learning at the elementary school level.